Nanophase-Separated Block-co-Polymers Based on Phosphonated Pentafluorostyrene and Octylstyrene for Proton-Exchange Membranes - Auffarth, Sebastian; Wagner, Maximilian; Krieger, Anja; Fritsch, Birk; Hager, Linus; Hutzler, Andreas; Böhm, Thomas; Thiele, Simon; Kerres, Jochen (ACS Materials Letters, 2023)
Nanophase separation into hydrophobic and hydrophilic domains in commercial perfluorosulfonic acid polymers promotes high conductivity by forming proton-conductive channels within a matrix. To transfer this beneficial phase separation to phosphonic acid functionalized ionomers, we combine phosphonated polypentafluorostyrene and flexible polyoctylstyrene in a di-block-co-polymer. We introduce a stepwise approach, including mesophase simulations, synthesis, and spectroscopic imaging. After the required block lengths were calculated, controlled radical polymerization led to a narrowly distributed block-co-polymer. The respective block-co-polymer membrane outperforms a phosphonated pentafluorostyrene blend concerning conductivity and water uptake. Stained membrane cross-sections revealed bicontinuous nanophase separation in the 13 to 25 nm range in transmission electron microscopy. The ion-conducting phosphonated polymer block assembled into an isotropic, three-dimensional gyroidal network across the membrane. Our stepwise approach is transferable toward other block-co-polymer systems featuring different monomers or functional groups. Applying the proposed principles allows for the prediction of structure-related phase separation while reducing the amount of synthesis work.
CRIS-Team Scopus Importer:2023-09-01